2006
DOI: 10.1016/j.jacc.2006.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Single-Beat Noninvasive Imaging of Cardiac Electrophysiology of Ventricular Pre-Excitation

Abstract: The individual cardiac anatomy model obtained for each patient enables accurate noninvasive electrocardiographic imaging of ventricular pre-excitation in patients with WPW syndrome. Noninvasive imaging of cardiac electrophysiology might be used as a complementary noninvasive approach to localize the origin and help identify and understand the underlying mechanisms of cardiac arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 17 publications
0
89
0
Order By: Relevance
“…From these measurements, an inverse problem that requires accurate knowledge of the geometry of the organs and structures located at and between the measurement surface and the heart muscle then needs to be solved. For example, newly developed electrocardiographic imaging methods based on high-density body surface potential maps are most promising (4,5) and clinically relevant (6,31) in that regard. Although possessing undeniable qualities, these methods require either ionizing exposure [i.e., three-dimensional computed tomography (5)] or MRI (6), which can be contraindicated for patients with pacemakers or stents.…”
Section: Discussionmentioning
confidence: 99%
“…From these measurements, an inverse problem that requires accurate knowledge of the geometry of the organs and structures located at and between the measurement surface and the heart muscle then needs to be solved. For example, newly developed electrocardiographic imaging methods based on high-density body surface potential maps are most promising (4,5) and clinically relevant (6,31) in that regard. Although possessing undeniable qualities, these methods require either ionizing exposure [i.e., three-dimensional computed tomography (5)] or MRI (6), which can be contraindicated for patients with pacemakers or stents.…”
Section: Discussionmentioning
confidence: 99%
“…However, inverse solutions that use homogeneous models seem to be less accurate in vivo. [21][22][23][24] The need to incorporate inhomogeneities in inverse mapping techniques, which could be used in a clinical setting has been widely debated. On the one hand, it has been shown that inhomogeneous inverse solutions correspond more closely with epicardial potential maps in the absence of noise.…”
Section: Why Does the Forward Problem Of Electrocardiography Matter?mentioning
confidence: 99%
“…Some qualitative models have also been developed [20,35] [40], and represents the excitation part of the monodomain RDE with two variables representing the depolarization and the repolarization of the cell membrane. Some analysis that measures the stability of excitable tissues in 2D using FHN and single or multiple noise sources is also presented [41,42].…”
Section: Electrical Excitation Methods Of Heart Tissuementioning
confidence: 99%